Conversations with Ella Kahu: Guest Editorial - Catherine Picton; Chi Baik (Student Success)
This special issue of Student Success celebrates the work of Professor Ella Kahu and her substantial contribution to the advancement of our collective understanding of student engagement. In June 2024 Professors Karen Nelson and Chi Baik, and Dr Cat Picton sat down with Ella for a reflective conversation about her work, and additional insights in her theorising and research on student experience and engagement. In this special issue, we present the interview transcript and showcase Ella’s key publications from her early theorising on the student engagement framework, through her collaborations with Professor Karen Nelson and the development of the educational interface to a series of empirical articles, exploring different dimensions of the student experiences, including students’ expectations of university, student belonging and metaphors of learning and life. This special issue takes us on a journey of the evolving scholarship and practice of Professor Ella Kahu. Part One presents the conceptual foundations of the framework of student engagement. Part Two explores the first-year student experience. Part Three delves in to teaching practices that promote student engagement.